Edinburgh and the Birth of British Evolutionism: A Peek behind a Veil of Anonymity. (20th June 2018) - Tanghe, Koen B; Kestemont, Mike
Abstract: Erasmus Darwin's evolutionary verses were isolated and ephemeral philosophical speculations. The real and academic birth of British evolutionism took place a couple of decades later in Edinburgh. It is probably no coincidence that the first fruits of this evolutionary theorizing were published during the approximately 2 years (1825–1827) that Erasmus's illustrious grandson Charles studied there: His evolutionary thinking was almost certainly more inspired by the first wave of British evolutionary theorizing than he later acknowledged or maybe even remembered. Unfortunately, we still don't know with certainty the identity of the authors of some of the key manifestations of this theorizing. Our identification, with the help of modern author verification software, of the authors of two of these anonymous evolutionary articles, published in 1826 and 1827, confirms that Darwin's geology professor Robert Jameson played a pivotal role in it.